Kawasan Penelitian Pendidikan Islam - Ahmad Mudzakkir; Syarifuddin Ondeng; Khalifah Mustami; Suarni (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This study aims to map the Islamic Education Research Area with a descriptive-analytical approach through library research methods. The field of Islamic education covers several main areas, including teaching materials, philosophy, history, institutions, systems, and curriculum. Each of these areas has unique characteristics and requires a different research approach to understand it comprehensively. Data were collected from sources in the form of books, scientific journal articles, and classical and contemporary references in Islamic education. Content analysis techniques were used to interpret the main concepts in each area, with source triangulation techniques applied to maintain the validity and objectivity of the data. The results of this study provide a systematic description that facilitates the mapping of Islamic education areas and offers relevant guidance for researchers and academics in determining research topics that focus on the development of Islamic education that is in accordance with contemporary needs.